CHANGES OF MICROSCOPIS DERMATITIS COMPLEX ON THE DOG PROVIDED OIL THERAPY NIMBA - Purnawan, Dewa Odiec; Suartha, I Nyoman; Oka Winaya, Ida Bagus (Buletin Veteriner Udayana; Vol. 14 No. 2 April 2022, 2022)
Complex dermatitis is inflammation of the skin caused by various types of agents such as fungi, ectoparasites, bacteria and congenital diseases that occur simultaneously so that the clinical signs shown are in the form of clinical combination of primary lesions and secondary lesions. The aim of the study was to observe changes in the microscopic skin of dogs with complex dermatitis patients after topical extract of neem oil. The sample consisted of 3 dogs that had moderate complex dermatitis. The three dogs were smeared with herbal extracts to the external part of the skin with lesions. Herbal extracts are given topically 2 times a day, morning and evening. On days 0, 7 and 15 a biopsy was performed on all three samples. Histopathological observations were carried out using a 100X and 400X binocular microscope. Histopathological examination shows changes in the form of hyperkeratosis, inflammatory cell infiltration in the form of basophils and neutrophils, ththosis, and ulcers. The results showed that administration of neural extracts affected dogs suffering from complex dermatitis or the administration of neem extracts can accelerate recovery in dogs suffering from complex dermatitis.